Penerapan Model Problem Based Learning Terhadap Hasil Belajar Siswa Kelas I SDN Pandeanlamper 01 Semarang - Dyah Setyowati; Noor Miyono; Ariestika Damayanti; Kanti Kartika Sari (Educatio, 2023)
Problem Based Learning is a learning model that integrates students in groups. Based on the results of the researchers' observations, it was found that in class I at SDN Pandeanlamper 01 Semarang there were still many students who did not understand the teacher's explanation. This was shown in the learning outcomes of many students who scored under the Learning Objectives Achievement Criteria (KKTP), namely 70. Of the 27 students, only 12 students achieved KKTP 70 with an average score of 66.5 and the percentage of classical completeness was only 44%. This study aims to determine the increase in student learning outcomes by applying the Problem Based Learning (PBL) model at SDN Pandeanlamper 01 Semarang. The type of research used is Classroom Action Research (CAR). The subjects in this study were 27 students in grade I at SDN Pandeanlamper 01 Semarang consisting of 14 boys and 13 girls. Data collection used tests, observation and documentation. The results showed that through the application of the Problem Based Learning model it could improve the learning outcomes of first grade students at SDN Pandeanlamper 01 Semarang. This can be seen from the average cycle I of 74.83 with a classical learning mastery of 66%. Cycle II, the average student learning outcomes increased from cycle I, which reached 79.66 with a classical learning mastery of 92%. So it can be concluded that through the application of the Problem Based Learning model it can improve the learning outcomes of class I students at SDN Pandeanlamper 01 Semarang.Keyword: Hasil Belajar, Problem Based Learning